"Most of the cases are very similar.": Documenting and corroborating conflict-related sexual violence affecting Rohingya refugees - Lindsey Green; Thomas McHale; Ranit Mishori; Linda Kaljee; Shahanoor Akter Chowdhury (BMC, 2022)
Abstract Background In August 2017, a large population of Rohingya from northern Rakhine state in Myanmar fled to Bangladesh due to "clearance operations" by the Myanmar security forces characterized by widespread and systematic violence, including extensive conflict-related sexual violence (CRSV). This study sought to document the patterns of injuries and conditions experienced by the Rohingya, with a specific focus on sexual violence. Methods Qualitative interviews were conducted with 26 health care professionals who cared for Rohingya refugees after their arrival in Bangladesh between November 2019 and August 2020. Results Health care workers universally reported hearing accounts and seeing evidence of sexual and gender-based violence committed against Rohingya people of all genders by the Myanmar military and security forces. They observed physical and psychological consequences of such acts against the Rohingya while patients were seeking care. Health care workers shared that patients faced pressure not to disclose their experiences of CRSV, likely resulted in an underreporting of the prevalence of sexual violence. Forced witnessing of sexual violence and observed increases in pregnancy and birth rates as a result of rape are two less-reported issues that emerged from these data. Conclusions Healthcare workers corroborated previous reports that the Rohingya experienced CRSV at the hands of the Myanmar military and security forces. Survivors often revealed their experiences of sexual violence while seeking care for a variety of physical and psychological conditions. Stigma, cultural pressure, and trauma created barriers to disclosing experiences of sexual violence and likely resulted in an underreporting of the prevalence of sexual violence. The findings of this research emphasize the importance of offering universal and comprehensive trauma-informed services to all refugees with the presumption of high rates of trauma in this population and many survivors who may never identify themselves as such.